Investigation of Vs – based liquefaction charts using a heavily preshaken silty sand centrifuge deposit. Issue 122 (July 2019) - Abdoun, T.; El-Sekelly, W.; Dobry, R.
Abstract: Preshaking by previous seismic activity can significantly affect the liquefaction resistance of saturated sands. Field evidence, cyclic laboratory testing and centrifuge modeling show that: (i) earthquake events that build up excess pore pressures short of liquefaction strengthen the soil; and (ii) liquefying earthquakes may weaken the soil. The paper presents the results of a centrifuge test (Experiment 2), where a 6 m saturated loose silty sand deposit was subjected to 52 successive base shakings. Three types of shakings were used: preshaking Events A, with a shaking duration of 5 cycles, and stronger Events B and C having a duration of 15 cycles, with Events C having the largest input accelerations. A total of 35 Events A, 9 Events B, and 8 Events C were applied at the base of the model in an alternating sequence. All Events C liquefied the deposit, with the Events B inducing liquefaction at the beginning but not at the end of Experiment 2. Events A generally induced excess pore pressures but not liquefaction. In addition to the pore pressures, horizontal accelerations, settlement and densification, and the soil shear wave velocity, Vs, were also monitored during the test. The results were compared with those of Experiment 1, reported in a previous publication, where a similar 6 m deposit of the same silty sand was subjected to a different sequence of shakings A and B which did not include any Event C. Conclusions are drawn on the effect of the strong Events C on the deposit's response. Events A, B and C of Experiment 2 are plotted on existing Vs –based liquefaction charts. The charts predict well the liquefaction response of the deposit at the beginning of Experiment 2. On the other hand, for shakings near the end of the test, the charts predict liquefaction for the Events B, which by this time have stopped liquefying the deposit due to the previous history of shakings. This result is consistent with the field evidence including the presence of a number of "false positives" in the charts for silty sand sites in the Imperial Valley of California, an area of intense seismic activity. Highlights: Earthquake events that build up excess pore pressures short of liquefaction strengthen the soil. Liquefying earthquakes may weaken the soil. Vs-based liquefaction triggering charts work well in recent fill but may be conservative for heavily preshaken deposits.